Pengaruh Promosi Jabatan dan Minat Nasabah Terhadap Kualitas Layanan Dengan Mediasi Strategi Pemasaran Pada Kredit Multiguna BMT NU BLORA - Salma Khoirunnisaa' Arribaat (Genius: Jurnal Ekonomi Dan Manajemen, 2025)
This research is motivated by the stagnation of the growth of Multipurpose Credit customers at BMT NU Blora Branch, allegedly due to a less than optimal position promotion system and low conversion of customer interest into loyalty. The research aims to analyze the influence of job promotion and customer interest on service quality with marketing strategy as a mediation variable. The study uses a causal explanatory quantitative approach with a cross-sectional survey design. The sample consisted of 150 respondents (active customers of Multipurpose Credit and marketing employees who had been promoted) selected through purposive sampling based on inclusion criteria. Data analysis was carried out with PLS-SEM using SmartPLS 4.0. The results showed that promotion had a significant positive effect on marketing strategy (path coefficient 0.452, p<0.01), customer interest had a significant positive effect on marketing strategy (0.387, p<0.01), and marketing strategy had a significant positive effect on service quality (0.561, p<0.01). Marketing strategies are proven to be a partial mediation both in the relationship between promotion and service quality (VAF = 38.7%) and customer interest in service quality (VAF = 42.3%). Research conclusion: Improving the quality of BMT NU Blora Multipurpose Credit services can be achieved through a marketing competency-based position promotion system and the use of customer interests as the basis for adaptive marketing strategies. Practical recommendations include post-promotion marketing training and periodic surveys of customer interest for targeted strategies